Nutrition preceptorship in the training process of resident nutritionists in Family and Community Health (Research, Society and Development, 2024)
The preceptorship of Health Residencies emerges as a professional qualification strategy joining theory and practice and promoting the linking of teaching to the principles and objectives of the Unified Health System. The study aimed to describe the activities carried out during core preceptorships and discuss the importance of this as a training and professional qualification tool for nutrition residents. It is a descriptive study, of the Experience Report type, on the training and professional qualification of Nutritionists through the Preceptorship of the Nutrition Center of the Multidisciplinary Residency in Primary Care, Family and Community Health at the State University of Rio Grande do Norte. In this way, preceptorship can be characterized as core and field, with the core being responsible for academic guidance linked to the content necessary for the professional core, performing important functions when developing reflections based on theoretical, theoretical-practical, and practical activities. The preceptorship broadens the vision to other areas of knowledge and performance in nutrition, favoring richer learning experiences in specialization, being a differentiator in the residency program, and preparing professionals for different scenarios.